INITIAL PUBLIC OFFERING /IPO/ IN MONGOLIA - ODBILEG Dorjdagva; ENKHTUVSHIN Dalantaibaatar (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Researchers have made various studies on why and when they shall publicly offered. The main difficulty in responding to these two questions due to identity of appropriate methodology and the lack of information by the companies to use the methodology. In this study, we investigate whether companies are doing IPOs in line with economic conditions. In other words, companies do IPOs when market conditions are good or the economy grows. If the market performance is insufficient, companies are keen to protect the financial situation of the company, rather to attract IPOs during the downturn. This paper comprises summary, introduction, theoretical and research sections, conclusions and reference.